HYPERFILTRATION OF POTASSIUM NITRATE THROUGH CLAY MEMBRANES UNDER RELATIVELY LOW-HEAD CONDITIONS - Hart M.; Whitworth T.M. (My University, 2005)
Much like reverse osmosis membranes, clays have been shown to exhibit reverse osmosis properties at high hydraulic heads. To determine if reverse osmosis was possible at lower hydraulic heads, potassium nitrate solutions were passed through thin clay layers at heads of 1.30 to 1.42 m. In each experiment, concentrations significantly increased due to partial solute rejection by the clay membranes. Concentration increases within the experimental cells were between 131% and 184%. Calculated values of the reflection coefficient ranged between 0.55 to 0.70, suggesting that these thin clay layers exhibited membrane effects. The results of these experiments suggest hyperfiltration may concentrate some dissolved contaminants from below to above regulatory limits in shallow aquifers bounded by a membrane-functioning aquitard or relatively low hydraulically conductive geologic strata. Hyperfiltration may also control nutrient distributions, creating subsurface microbial “hotspots”. Consideration of hyperfiltration effects may ultimately lead to a clearer understanding of many subsurface processes, both shallow and deep, including contaminant fate and transport, subsurface microbiology, natural bioremediation and attenuation, redox, rock–water interaction, and groundwater chemistry.